Improvement of Fasting Plasma Glucose Level After Ingesting Moderate Amount of Dietary Fiber in Japanese Men With Mild Hyperglycemia and Visceral Fat Obesity. (1st June 2013) - Kobayakawa, Akira; Suzuki, Tomoo; Ikami, Takao; Saito, Morio; Yabe, Daisuke; Seino, Yutaka
ABSTRACT A double-blind, randomized, controlled study was conducted to evaluate the effects of a moderate amount of dietary fiber intake on fasting plasma glucose level and physical characteristics in Japanese men with mild hyperglycemia and visceral fat obesity. Thirty men with mild hyperglycemia (>5.6 mmol/L) and visceral fat accumulation (>100 cm2) ingested 7.5 g/day of dietary fiber for 12 weeks. An abdominal computed tomography scan was performed at baseline and at week 12. Blood was drawn every 4 weeks. In the test food group, fasting plasma glucose level was reduced with time, and the difference between the test food group and placebo group was statistically significant at week 12. Body weight and body mass index were also reduced with time, but visceral and subcutaneous fat areas did not change significantly during the study period. The results suggest that even a moderate amount of dietary fiber intake may be beneficial for managing the fasting plasma glucose level concomitant with insulin resistance, body weight, and body mass index in Japanese men with mild hyperglycemia and visceral fat obesity.